ANALISIS KELAYAKAN USAHA PETERNAKAN AYAM KAMPUNG UNGGUL MENGGUNAKAN KONSEP HAMDI’S METHOD - Agustin, Hamdi; Syukri, Edi; Hamdi, Lathifa Miftahul Jannati; Hamdi, Luthfia Ahluljannati (Universitas Bina Bangsa, 2024)
A superior native chicken farming business that has great potential to be developed in order to meet the needs of animal food. The purpose of this study was to test whether the assessment of the feasibility study of the business with Hamdi's method consisting of GVM and GI provides the same decision results as the assessment using the conventional method consisting of NPV and PI. This study attempts to test the superior native chicken farming business plan in Tapung District, Kampar Regency, Riau Province. The results of this assessment will be useful as a consideration in making business development decisions. The financial feasibility analysis calculated is Payback Period (PP), Net Present Value (NPV), Profitability Index (PI), Gold Value Method (GVM) and Gold Index (GI). The results of the analysis show that the Net Present Value (NPV) is IDR 122,963,738, Profitability Index (PI) 2.01, Gold Value Method (GVM) 4.57 grams, Gold Index (GI) 1.04. The results of this analysis indicate that this business is feasible to be developed based on financial aspects. Using Hamdi's Method can be used in assessing business feasibility, where the calculation results are the same as NPV and PI